The impact of online customer experience (OCE) on service quality in Malaysia - Salimi, Mehrdad Salehi Meysam; Haque, A. K. M. Ahasanul (IDOSI Publication, 2013)
Nowadays, online product communities have turned into an integral element of Web-based strategies of many corporations. This facility allows customers to be kept in touch with producer companies. Hence, these conditions raising the importance of customer experience in the online environment as well. This quantitative research aimed to develop a new framework to illustrate the determinants of service quality from customer experiences perspective in the online environment in Malaysia. To conduct this study, the four dimensions of customer experience, namely Pragmatic Experience, Sociability Experience, Usability Experience and Hedonic Experience, were at first identified from review of literature. Subsequently, gathering data from 148 respondents in Selangor (Malaysia) was done and the Multiple Regression Analysis was applied to check the associations between each variable and service quality. The developed model covered the 63.7% of variation and showed that service quality is affected by the four identified independent variables significantly.